Integrating Ethnomathematics into Primary Mathematics Instruction to Enhance Students’ Mathematical Communication Skills - Nurhanan, Nurhanan; Santoso, Erik (Al-Mufid, 2023)
This study investigates the impact of integrating ethnomathematics into primary school mathematics instruction on students’ mathematical communication skills. Motivated by the lack of contextualized learning environments that affirm students’ cultural identities and foster expressive competence, the research adopts a quasi-experimental design with pretest-posttest control groups. Participants consisted of 60 fifth-grade students in West Java, Indonesia, divided into an experimental group taught through ethnomathematics-based learning and a control group taught with conventional methods. A validated mathematical communication test assessed students’ abilities to express ideas verbally, symbolically, and visually. Results show a statistically significant improvement in both groups; however, the experimental group demonstrated a considerably higher effect size (Cohen’s d = 1.97) than the control group (Cohen’s d = 1.25). Moreover, independent t-test results (t(58) = 6.851, p < .001) confirm that culturally contextualized instruction more effectively fosters communication-rich learning environments. The study highlights the importance of meaningful cultural contexts in enhancing mathematical communication and calls for broader adoption of ethnomathematics-based pedagogies. Limitations and recommendations for future research are also discussed.